To the intraspecific structure of Carabus (Morphocarabus) brinevi Kabak, 2014 (Coleoptera: Carabidae) - I.I. Kabak (Кавказский энтомологический бюллетень, 2021)
The intraspecific structure of Carabus (Morphocarabus) brinevi Kabak, 2014 from Chinese part of the Mongolian Altai Mountain Range is discussed. A new subspecies is described – C. brinevi kanasensis subsp. n. from left bank of Kanas Lake (Xinjiang-Uygur Autonomous Region of China). The new subspecies differs from the nominotypical one in the larger body size, widely depressed lateral sides of pronotum, presence of supplimentary lateral setae of the latter, dark colouration of tibiae, as well as in the convex distally right lateral wall of the aedeagal tube, and in the endophallus structure. The subspecific rank of Carabus (Morphocarabus) brinevi subsp. altaicola Deuve et Tian, 2019, stat. n. is established